On the estimation of the rate of convergence in the integrallimit theorem - Banys, J. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. И. Банис. Оценка скорости сходимости в интегральной предельной теореме J. Banys. Konvergavimo greičio įvertinimas integralinėje ribinėje teoremoje